New reactive sites enabled via an allyl-to-allyl 1,4-Rh(III) migration - Korkis, Stamatis E. (2018)
The Rh(III)-catalysed oxidative C–H allylation and homoallylation of N-acetylbenzamides with 1,3-dienes is described. The presence of allylic hydrogens cis to the less substituted alkene of the 1,3-diene is important for the success of these reactions, though not essential. With the assistance of reactions using deuterated 1,3-dienes, a proposed mechanism is provided. The key step is postulated to be the first reported examples of allyl-to-allyl 1,4-Rh(III) migration. Importantly, migration to primary or secondary allylic position results in allylation products, whereas migration to a tertiary position leads to homoallylation. Using 1,4-dienes as the coupling partner, N-tosylbenzamides are homoallylated. Preliminary results indicate a mixture of isomer products, with major isomer resulting from an allyl-to-allyl 1,4-Rh(III) migration.